QUESTIONING STRATEGIES AND THE CONSTRUCTION OF CONTEXT IN CLASSROOM TALK - Jariah Mohd Jan; Rosli Talif (The English Teacher, 2005)
This paper focuses on the teacher’s questioning strategies in order to elicit responses that contribute to the construction of context in classroom discussion. It also examines the social power relations of the classroom teacher and students. The findings of the children’s talk in this study suggest that preschool children do observe rules for public conduct and for a share in the construction of context with their peers and teachers. They also develop extensive repertoires of speech acts and use speech strategically to manipulate others, to guide their activity, and most importantly to construct meaning in context.